Low Cost Carriers (LCC) in the Indian Aviation Space: A Contemporary Indian Perspective - Ghoshal, Anupama; Mathews, Soney (2015)
The paper discusses in case study format the present struggle in the low cost airlines market with players like Indigo, SpiceJet, Jet Airways and GoAir etc. The case describes the contemporary events, challenges and opportunities prevailing in the Indian aviation sector with special focus on the low cost carries (LCC). The case also outlines the implications of the factors affecting LCC operations for the contemporary Indian consumer. The present case study can be used for classroom discussions in marketing, strategic marketing and consumer behavior to describe the strategies of the LCC players in contemporary Indian market. The content of the case study can also be used to further develop detailed cases on the individual airline companies competing in the LCC space.